Evaluation of peripheral intravenous line securement devices under clinically relevant loading and perspiratory conditions - George K. H. Morgan; Maegan Spiteri; Spyros Masouros (PLoS ONE, 2026)
Peripheral vascular access devices (PVADs) and their associated intravenous (IV) lines are widely used in clinical care. Securement devices are typically employed to prevent accidental dislodgement and complications such as occlusion and phlebitis. Despite the wide use of securement devices, there are no standardised methods for evaluating their actual ability to secure IV lines. This study assessed the securing ability of four commercially available IV line securement devices – Grip Lok, Javelo, micropore tape, and IV bracelet – under controlled laboratory conditions. First, all four devices were tested for resistance to axial pull-out forces using a uniaxial materials testing machine across ten participants. Participant comfort during testing was assessed via questionnaire. Grip-Lok and Javelo exhibited significantly greater axial pull-out strength than the other two devices (p-adj < 0.001), and were progressed to further testing, consisting of off-axis loading at 90°, 135°, and peel-off, and axial pull-out under simulated perspiration conditions. No significant differences were observed between Grip Lok and Javelo under loading in 90° and 135°. Javelo demonstrated superior performance in both peel-off and perspirant conditions (p-adj < 0.05). Javelo was rated the most comfortable by 60% of participants. The results highlight the need for incorporating realistic loading conditions and comfort metrics when evaluating the performance of infusion line securement aids. Furthermore, the results provide evidence that using a non-adhesive based device, particularly in patients with marked diaphoresis might provide more infusion line security, though further study is required.